Alcohol production in yeast isolates from gracilaria verrucosa and kappaphycus alvarezii - Grecia, Glenn Landazabal Jr (University of the Philippines Visayas, College of Arts and Sciences, Division of Biological Sciences, 2009)
The feasiblity of wine production from the red seaweed Gracilaria verrucosa using alcohol-producing yeast Saccharomyces cerevisiae. Thi study will test the wine production capability of the alcohol-producing yeast isolates from seaweed inoculated singly or in combinations to establish awareness of its wine-producing use in the future. this study could help future seaweed wine producers in determining the more efficient seaweed wine producer